Historic timber roofs in Belgium: overview of materials and structures (1150-1960) - Louis Vandenabeele (Tema, 2022)
Belgium has a remarkable heritage of historic timber roofs that can be traced back to the 12th century. This contribution provides a review of 60 years of research on Belgian timber roofs and outlines their developments from 1150 to 1960. The focus is firstly put on wood resources, a crucial parameter for roof construction in a scarcely forested landscape. Then, the evolution of structural concepts over 800 years is discussed based on illustrations of remarkable roofs. Moreover, this broad overview raises several questions that open up new prospects for future investigations.